2018
DOI: 10.2214/ajr.17.18472
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytomas Versus Adenoma: Role of Venous Phase CT Enhancement

Abstract: A significant subset of pheochromocytomas mimics adenomas on absolute or relative percentage washout calculations. However, nodules with venous phase enhancement of 85 HU or more are much more likely to be pheochromocytomas than adenomas, regardless of whether the lesion shows absolute or relative percentage washout compatible with a lipid-poor adenoma. The typical values of absolute and relative percentage washout of adrenal adenoma should be interpreted along with the venous phase enhancement value to avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Many efforts have been made to further evaluate the nature of undetermined adrenal lesions using various imaging modalities, but with questionable outcome [6][7][8][9][10][11][12][13][14] . A correct diagnosis is especially important in pheochromocytomas 15,16 and adrenocortical carcinomas 17,18 since hormonal activity or early metastatic spread, respectively, can lead to significant morbidity and mortality [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to further evaluate the nature of undetermined adrenal lesions using various imaging modalities, but with questionable outcome [6][7][8][9][10][11][12][13][14] . A correct diagnosis is especially important in pheochromocytomas 15,16 and adrenocortical carcinomas 17,18 since hormonal activity or early metastatic spread, respectively, can lead to significant morbidity and mortality [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Pheochromocytomas are characteristically, although not uniformly, large, heterogeneous masses with the areas of necrosis and cystic changes (15). Prior studies have reported that pheochromocytomas were significantly more likely to contain necrosis compared to adenomas (10,13). For example, Park et al.…”
Section: Discussionmentioning
confidence: 91%
“…reported that 66% of pheochromocytomas were misclassified as adenoma on dedicated adrenal CT. In that study, the criteria for adenoma were APEW > 60% and RPEW > 40% (13). A PP enhancement ≥ 85 HU was found to be much more likely to be pheochromocytoma than adenoma.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations